The Effect Of Brush-Induced Injury On Molecular Expression Profile Of Rabbit Airway Epithelium During Regeneration And Repair - Ahmad Zaeri , Latahir (2014)
Tracheal epithelium is equipped with well-balanced defensive features to keep the body away from harmful particles. Upon an injury, the cellular repairing process undergone with the involvement of cell migration and spreading, proliferation, and redifferentiation. Epitelia trakea mempunyai ciri-ciri pertahanan yang mampu untuk melindungi dari partikel-partikel berbahaya. Semasa berlakunya kecederaan, proses pembaikpulihan sel-sel yang bertanggungjawab yang mana ianya melibatkan proses-proses seperti sel migrasi dan penyebaran, proliferasi, dan pembezaan semula sel-sel.